2019
DOI: 10.46653/jhst190202045
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Fruit Bagging for the Control of Insect-Pests Complex and its Impact on Quality of Mango Fruits

Abstract: Mango (Mangifera indica L.) is famous among all fruits because of its taste, variety and color. However, the quality of mango fruits is mainly deteriorated by insect-pests complex. The study was performed to evaluate bagging effects on insect-pests complex, yield and quality of mango fruits at private mango orchards located in Multan district. A mango cultivar, Anwar Rataul was selected, and the fruits were bagged during 1st week of May (at stone size stage) to 1st week of July 2017 (at maturity stage). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…), we found that bagged mangoes were 9.6% (cloth bags) and 11.1% (paper bags) heavier than controls but only by about 3% greater in volume, given that sphericity was not different among the treatments (Table 2). These results are consistent with those previously reported by several authors who indicated that bagging increases fruit weight and total yield [17,24,29,35,39,40].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…), we found that bagged mangoes were 9.6% (cloth bags) and 11.1% (paper bags) heavier than controls but only by about 3% greater in volume, given that sphericity was not different among the treatments (Table 2). These results are consistent with those previously reported by several authors who indicated that bagging increases fruit weight and total yield [17,24,29,35,39,40].…”
Section: Discussionsupporting
confidence: 93%
“…Hoffman et al [16] also described an increase in the skin area with yellow color and a decrease in reddish area in Keitt cv., whereas Anwar Rataul cv. fruits bagged with brown paper bags showed a more yellowish color than control or butter paper bags [40]. Finally, Wu et al [41] found that lightness and chroma were remarkably higher, while hue angle was significantly lower than controls, and that a single white bag could be a promising practice for improving coloration.…”
Section: Discussionmentioning
confidence: 98%
“…Bagging can promote fruit coloring and improve fruit surface smoothness. In addition, bagging can also reduce the direct pollution of pesticides, dust, and prevent diseases and attack by pests and birds [17]. Bagging has become an important technique in the production of high-quality and pollution-free fruits.…”
Section: Discussionmentioning
confidence: 99%
“…These ‘push‐pull’ strategies largely involve the use of nonlethal materials to conserve parasitoids and the weaver ant species ( Oecophylla spp.) against fruit flies in fields 149–155 . On the other hand, zero tillage, including application of weedicides, will conserve EPNs in soils because EPNs are not generally affected by pesticides, except some nematicides 156 .…”
Section: Considerations For Future Researchmentioning
confidence: 99%
“…Bagging fruits on trees reduces exposure of fruits to fruit flies and pathogens [e.g. anthracnose disease‐causing Colletotrichum gloeosporioides Penzig & Saccardo (Glomerellales: Glomerellaceae)] 153,154,161 . The latter is a destructive fungal pathogen that reduces fruit set, increases premature fruit drop and/or causes blemish to quality of fruits in many countries across SSA (authors' personal observations).…”
Section: Considerations For Future Researchmentioning
confidence: 99%